Effects of FR-91 on Immune Cells from Healthy Individuals and from Patients with Non-Hodgkin Lymphoma. (5th July 2009) - Lombardi, V. R. M.; Martínez, E.; Chacón, R.; Etcheverría, I.; Cacabelos, R.
Abstract : The immune system is subject to destruction and dysfunction as a result of attacks by pathogenic and environmental agents. In addition, many clinical situations exist in which it is desirable to stimulate or suppress the immune system. The present study evaluated the screening efficacy of flow cytometric lymphocyte subset typing in peripheral blood mononuclear cells from healthy individuals (HI) and from patients with non-Hodgkin lymphoma (NHL) treated with different concentrations of FR-91, a standardized lysate of microbial cells belonging to the Bacillus genus, and in vitro cytokine production. Increased expression of subset markers (CD3, CD4, CD8) in NHL and CD3 in HI suggests an immunomodulating effect of FR-91. In addition the results of cytokine production also demonstrated a clear effect of FR-91 on both populations. A significant increase of IL-6, IL-12, IFN-γ and TNF-α was observed in the HI group after treatment with FR-91. In a similar manner an increase of IL-2, IL-6, IL-12, IFN-γ and TNF-α was also observed in the NHL group. In conclusion FR-91 seems to affect lymphocyte subpopulations, in vitro cytokine production, as well as mitogen-induced lymphocyte activation in a dose-dependent manner in both healthy individuals and NHL patients.